SISTEM PENGENDALIAN PARKIR MENGGUNAKAN SENSOR SWITCH - Siswanto, Siswanto; Rohmawan, Eko Prasetyo; Kalsum, Toibah Umi (UNIVED Press, 2013)
Developments in science and technology is now becoming more sophisticated with the advent of modern tools, for example, is a computer. The use of computers in society is no stranger to either diperkantoran, homes, and other pasilitas. In this case the computer is connected to the existing components in the computer that serves as a tool insert (input) and the tool keluaraan (output) through the computer components can be used to control the hardware (hardware) and other purposes. Parking control system uses sensors Swicth are now widely applied disupermarket, and other objects, especially banks, offices that serve to simplify the calculation of the cost of parking and security support with some limitations that are likely to cause problems in terms of security, parking entrance queue, the queue out parking and some other things we do not want.But the satisfaction and comfort of use in terms of services such as parking and security queues of vehicles are not so considered by pengelolah parking at this time, benefited business interests more than the interests of consumers are less noticeable, to give satisfaction for the use of parking that can minimize the queue at the gate entrance and out the door by accelerating the process of entry, exit, in order to give priority to the interests of consumers so that consumers feel comfortable in their vehicle memakir better than the manual way.